Duke's handbook of medicinal plants of Latin America - Duke, James A (Taylor & Francis, 2012)
Year-round moderate temperatures, abundant rainfall, and rich soils make tropical Latin America home to nearly 100,000 of the world's 300,000 known species of plants, and therefore home to untold numbers of potential cures. This book focuses on 500 of the most well-known and well-studied plants.